Religion in Geschichte und Gegenwart online: RGG (Brill, 2015)
Religion in Geschichte und Gegenwart 4 Online is the online version of the 4th edition of the definitive encyclopedia of religion worldwide: the peerless Religion in Geschichte und Gegenwart 4 (RGG4) (Mohr Siebeck, 1998-2007). This great resource continues the tradition of deep knowledge and authority relied upon by generations of scholars in religious, theological, and biblical studies. Religion in Geschichte und Gegenwart 4. indisputably belongs to the small class of essential reference works.
Gesehen am 28.07.15
Keywords: Datenbank